Mechanics of seabed liquefaction and resolidification - Sawicki, A. (Archives of Mechanics, 2014)
The problem of pore water pressure changes in the seabed is considered. Two mechanisms of pore pressure changes are distinguished. The first is caused by external excitations, such as earthquakes, when pore pressure is gradually generated, leading to liquefaction. The second mechanism is caused by water waves, and it leads to cyclic changes in pore water pressure and the mean effective stress. Under certain conditions, when the effective stress path tends to exceed the failure condition, the regrouping of effective stresses takes place, as the soil should accommodate to new conditions. Then, the mechanism of resolidification of the seabed is described. It is concluded that after resolidification, the seabed is in a virgin state, as liquefaction erases the previous history of the seabed structure. A critical discussion of selected existing approaches to the problem of pore-pressure changes and the mechanism of liquefaction is presented in detail, in the form of extensive appendices. Some of these appendices deal with the crucial aspects of the mechanics of liquefaction such as, for example, the drained/undrained conditions.